2004
DOI: 10.1074/jbc.m310442200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Diversity of the Rhodanese Homology Domain

Abstract: Escherichia coli has eight genes predicted to encode sulfurtransferases having the active site consensus sequence Cys-Xaa-Xaa-Gly. One of these genes, ybbB, is frequently found within bacterial operons that contain selD, the selenophosphate synthetase gene, suggesting a role in selenium metabolism. We show that ybbB is required in vivo for the specific substitution of selenium for sulfur in 2-thiouridine residues in E. coli tRNA. This modified tRNA nucleoside, 5-methylaminomethyl-2-selenouridine (mnm 5 se 2 U)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
77
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 48 publications
3
77
0
Order By: Relevance
“…The ATP requirement of the s 2 T reaction was clearly observed in this system, and this is consistent with the fact that some tRNA modification enzymes are derived from P-loop ATPases (e.g. ThiI (s 4 U8 synthesis (32,36)), MnmA (mnm 5 s 2 U34 (31)), TilS (lysidine 34 (37)), TtcA (s 2 C32 (38)), and YbbB (5-methylaminomethyl-2-selenouridine 34 (39)). It has been demonstrated that some of these enzymes bind the substrate tRNA (31,32,37,39) and activate the target nucleoside with ATP, forming an adenylate intermediate (40).…”
supporting
confidence: 58%
See 1 more Smart Citation
“…The ATP requirement of the s 2 T reaction was clearly observed in this system, and this is consistent with the fact that some tRNA modification enzymes are derived from P-loop ATPases (e.g. ThiI (s 4 U8 synthesis (32,36)), MnmA (mnm 5 s 2 U34 (31)), TilS (lysidine 34 (37)), TtcA (s 2 C32 (38)), and YbbB (5-methylaminomethyl-2-selenouridine 34 (39)). It has been demonstrated that some of these enzymes bind the substrate tRNA (31,32,37,39) and activate the target nucleoside with ATP, forming an adenylate intermediate (40).…”
supporting
confidence: 58%
“…ThiI (s 4 U8 synthesis (32,36)), MnmA (mnm 5 s 2 U34 (31)), TilS (lysidine 34 (37)), TtcA (s 2 C32 (38)), and YbbB (5-methylaminomethyl-2-selenouridine 34 (39)). It has been demonstrated that some of these enzymes bind the substrate tRNA (31,32,37,39) and activate the target nucleoside with ATP, forming an adenylate intermediate (40). Thus, a tRNA binding ATPase might also be involved in s 2 T54 synthesis, and/or ATPase(s) may be involved also in sulfuractivating steps.…”
mentioning
confidence: 99%
“…The role of YnjE so far remained enigmatic for E. coli. In total, with the exception of ThiI and YbbB, which are required for thiamine/thiouridine and selenouridine biosynthesis (18,20), respectively, little is known about the in vivo role of the other rhodaneses. It was of interest to identify whether, by analogy to Moco biosynthesis in humans, a rhodanese-like protein acts as a mediator between IscS and MoaD for the formation of the thiocarboxylate group of MPT synthase in conjunction with MoeB.…”
mentioning
confidence: 99%
“…Furthermore, catalytic or inactive rhodanese domains are also found in other proteins, such as ThiI (16), or in Cdc25 phosphatases (17). In the E. coli genome, eight genes have been identified coding for proteins containing a rhodanese-like protein domain bearing a conserved cysteine residue as a potential active site for persulfide formation (15,18). Three of them code for the proteins GlpE, PspE, and YgaP that are composed of only a single rhodanese domain.…”
mentioning
confidence: 99%
“…In tRNA mnm5s2UUU . 2 When selenium is available in the growth medium, sulfur at position 2 may be replaced by selenium in a reaction dependent on SelD and YbbB (17)(18)(19). It has been shown that modifications at position 2, but not at position 5, are important for aminoacylation of tRNAs (20)(21)(22), whereas modification in both 2-and 5-positions function in the codon recognition process (17,18,(22)(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%